Corporate governance reform and overstatement of compliance: Illustrations from an emerging economy. Issue 4 (14th August 2020) - Islam, Md Tariqul; Rahman, Mahfuzur; Saha, Shrabani
Abstract: This paper examines the effect of corporate governance (CG) reform on the window dressing of compliance in the context of an emerging economy, Bangladesh. In particular, this study investigates the true level of compliance concerning the three internal governance mechanisms, such as board independence, CEO duality and formation of audit committee before and after the reform enacts. By using content analysis of 194 non‐financial listed companies between 2007 and 2017, this study observes the extent of overstatements in compliance statements along with the nature of firms that are involved in it. After the regulatory shift in 2012, requiring more independent directors into the board and external certification of compliance statements, it was found that the extent of window dressing in compliance statements declined considerably over time. Moreover, government firms are found to make more proportionate overstatements compared to family and others (non‐family and foreign companies). counterparts. The fall in window dressing indicates that the companies' fabricating efforts in CG compliance are challenged by the regulatory change in a formal legal environment.